The Role of Educational Attainment in Shaping Perceptions of Climate Change Mitigation and Adaptation Strategies - Aryal, Pitambar; Gangal, Meenu; Karki, Tej Bahadur (International Research Journal of MMC, 2025)
Global community has been witnessing increases in atmospheric temperature along with climate variability and change. Human activities are primarily responsible causing temperature raise consequently having weather related extreme events. Nepal, being diverse topography and climatic zones, experiencing severe impact of climate change. Rapid melting of ice in Himalaya region, bio diversity loss, drought and heavy rainfall are becoming regular phenomena in the recent past. The climate variability and change causing climate induced disasters impacting livelihoods of rural population of Nepal. Mitigation and adaptation measures initiated at local level play a pivotal role in reducing impact of climate change. The mitigation and adaptation measures could be initiated after having thorough understanding of community people about their perception on this. For this, education of local community may maximize their understanding which play a critical role in shaping their knowledge, perception and understanding about climate change, its impact and mitigation and adaptation measures. In this background, a study was carried out among 428 households of ward no 5, 6 &7 of Sarawal Rural Municipality, Nawalparasi West, Nepal. Out of 428, 33.4% were illiterate, 26.2 literate (informational education), 26.9% primary (up to 8 class) and 13.6% were high school and above. The main purpose of this study was to better understand about perception of study population on climate change mitigation and adaptation measures which could be initiated at local level. The study was designed in 5-point Likert scale having eight different mitigation and adaptation measures. A null hypothesis was formulated for this study indicating that there is no direct association between level of education and community perception about climate change mitigation and adaptation measures. The findings of study denote that there is association between perception of climate change mitigation measures and level of education. While comparing the educational level and their response, p-value is <0.05, indicating that it is statistically significant meaning there is a significant association between education and their level of understanding thus null hypothesis is rejected.